Modular Systems for Building Renovation - Ulugbek, Tojiboev; Marjona, Kamilova (Indonesian Journal Publisher, 2024)
The article discusses the methodology and technology of installing a new facade system on the old facade of the building, improving the appearance of the building and protecting the old facade, including the prevention of many problems. This research employs an analytical descriptive approach by gathering information on the methodology and technology used in installing modular facade systems on existing buildings. Data is collected through literature review and case studies of successfully implemented building renovation projects. The analysis results indicate that the use of modular systems in building renovation provides numerous benefits, including improved construction efficiency, cost and time reduction, as well as enhanced durability and aesthetics of the building. Moreover, the use of modular systems enables more flexible design adjustments according to the existing architectural context. The utilization of modular systems in building renovation brings positive impacts in enhancing the building's appearance while safeguarding the original facade and preventing various construction issues. By providing more efficient and flexible solutions, modular systems unlock significant potential in sustainably and aesthetically renewing existing building structures.